Galactana sulfatada não-citotóxica da alga marinha Gracilaria cornea J. Agardh Polariza macrófagos para um fenótipo antitumoral in vitro e inibe o crescimento tumoral em um modelo de melanoma Murino - Teles, Felipe Barros (2024)
Seaweeds are known for producing various bioactive compounds, among which we can highlight sulfated polysaccharides (SP). SP are biomolecules that have various biological activities that have already been described. In relation to cancer, the ability of certain SP to stimulate innate immunity cells, especially to activate macrophages (Mfs) towards an anti-tumor phenotype, represents a promising approach that has attracted increasing interest from the scientific community due to its therapeutic potential. The aim of the present study was to assess whether sulfated galactans (SG) - a PS found in red seaweeds - obtained from the species Gracilaria cornea (SG-Gc) and Solieria filiformis (SG-Sf), were able to activating a lineage of murine macrophages (RAW 264.7) towards an antitumor phenotype. The results showed that both SG-Gc and SG-Sf induced the production of nitric oxide (NO) in RAW 264.7, suggesting their activation to a pro-inflammatory phenotype (similar to M1). Furthermore, although SG-Gc did not directly inhibit the proliferation of the murine melanoma cell line (B16-F10), the medium-conditioned RAW 264.7 incubated with SG-Gc (MC-SG-Gc) was able to inhibit the proliferation of B16-F10. This result suggests that, although SG-Gc does not show direct cytotoxicity against B16-F10, it may exert an antitumor effect mediated by macrophage activation. Due to its bioactive profile, SG-Gc was selected for further testing. Subsequent phenotypic characterization experiments revealed that SG-Gc increased the expression of MHC class II and CD86 surface markers, as well as increasing the expression of iNOS (intracellular marker). This result further reinforces the immunostimulant potential of SG-Gc on macrophages. In a murine melanoma model, the administration of SG-Gc at a dose of 25 mg/kg, intraperitoneally (i.p) in C57BL/6 mice over 14 days promoted a reduction of approximately 60% in tumor weight compared to the negative control group. In addition, histopathological analyses showed an increase in spleen weight accompanied by disorganization of the white pulp, corroborating the hypothesis that SG-Gc exerts an anti-tumour effect by stimulating the immune system. Finally, no toxic effects were observed throughout the treatment of the animals with the sample, indicating its safety for potential therapeutic use. In summary, our study emphasizes the promising antitumor and immunomodulatory properties of SG, especially the G. cornea species. While we continue to study the mechanisms underlying the observed pharmacological effects, our work contributes to the growing body of evidence supporting the therapeutic potential of polysaccharides of marine origin for the treatment of cancer.